Adoption of Improved Technologies of Kharif Crops in Arid Zone - Singh, Bhagwan (Annals of Arid Zone, 2016)
A study was conducted in four districts namely, Jodhpur, Pali, Bikaner and Jaisalmer of Rajasthan to study the adoption of improved technologies of kharif crops and to find out the relationship between socio-economic characteristics of the farmers and adoption of technology. The study revealed that extent of adoption of improved technologies of kharif crops was between 29 to 32%. The study also revealed that majority of the farmers had adopted high yielding varieties, seed treatment, application of nitrogenous and phosphatic fertilizers and plant protection measures to a lesser extent. Key words: Adoption, improved technology, kharif crops.